EFL TEACHERS’ PERCEPTIONS AND STRATEGIES IN IMPLEMENTING LEARNER AUTONOMY - YUZULIA, IRZA (Linguists : Journal of Linguistics and Language Teaching, 2020)
Learner autonomy is essential in order to make the students become responsible for their own learning. However, it does not mean that the students are fully independent of their own learning. The teacher’s roles and presence are important to introduce the students to the concept of autonomous learning as well as to promote strategies to foster learner autonomy. This study aims to find out the teachers’ perceptions of the concept of learner autonomy and to find out the strategies used by the experienced and the novice English teacher to implement learner autonomy. This qualitative study was conducted in public senior high schools in Bandung. An experienced and a novice English teacher were involved in this study. The data in this study were collected through observation, interview and questionnaire. The study revealed that experienced and novice teacher hold almost the same perceptions that autonomy means the students’ active role in managing their own learning. The teachers pointed out that autonomous learning gives benefits to students’ learning. However, the experienced teacher was more optimist than the novice teacher regarding the possibility to promote learner autonomy which affects their classroom practices to promote learner autonomy. It is proved that the experienced teacher offers more strategies since she believed that learner autonomy is applicable for all language learners despite students' ages, levels of proficiency and cultures. It was found that the teachers used blogs, self-journal, videoconference and collaboration as strategies to promote learner autonomy.